DC-SIGN (CD209) Promoter −336 A/G (rs4804803) Polymorphism Associated with Susceptibility of Kawasaki Disease - Hong-Ren Yu; Wei-Pin Chang; Lin Wang; Ying-Jui Lin; Chi-Di Liang; Kuender D. Yang; Chiu-Ming Kuo; Yi-Chuan Huang; Wei-Chiao Chang; Ho-Chang Kuo (The Scientific World Journal)
Kawasaki disease (KD) is characterized by systemic vasculitis of unknown etiology. High-dose intravenous immunoglobulin (IVIG) is the most effective therapy for KD to reduce the prevalence of coronary artery lesion (CAL) formation. Recently, the α2, 6 sialylated IgG was reported to interact with a lectin receptor, specific intracellular adhesion molecule-3 grabbing nonintegrin homolog-related 1 (SIGN-R1) in mice and dendritic cell-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN) in human, and to trigger an anti-inflammatory cascade. This study was conducted to investigate whether the polymorphism of DC-SIGN (CD209) promoter −336 A/G (rs4804803) is responsible for susceptibility and CAL formation in KD patients using Custom TaqMan SNP Genotyping Assays. A total of 521 subjects (278 KD patients and 243 controls) were investigated to identify an SNP of rs4804803, and they were studied and showed a significant association between the genotypes and allele frequency of rs4804803 in control subjects and KD patients (P=0.004 under the dominant model). However, the promoter variant of DC-SIGN gene was not associated with the occurrence of IVIG resistance, CAL formation in KD. The G allele of DC-SIGN promoter −336 (rs4804803) is a risk allele in the development of KD.